Core–Shell Microfiber Encapsulation Enables Glycerol-Free Cryopreservation of RBCs with High Hematocrit - Qin, Xianhui; Chen, Zhongrong; Shen, Lingxiao; Liu, Huilan; Ouyang, Xilin; Zhao, Gang (Nano-Micro Letters, 2023)
Cryopreservation of red blood cells (RBCs) provides great potential benefits for providing transfusion timely in emergencies. High concentrations of glycerol (20% or 40%) are used for RBC cryopreservation in current clinical practice, which results in cytotoxicity and osmotic injuries that must be carefully controlled. However, existing studies on the low-glycerol cryopreservation of RBCs still suffer from the bottleneck of low hematocrit levels, which require relatively large storage space and an extra concentration process before transfusion, making it inconvenient (time-consuming, and also may cause injury and sample lose) for clinical applications. To this end, we develop a novel method for the glycerol-free cryopreservation of human RBCs with a high final hematocrit by using trehalose as the sole cryoprotectant to dehydrate RBCs and using core–shell alginate hydrogel microfibers to enhance heat transfer during cryopreservation. Different from previous studies, we achieve the cryopreservation of human RBCs at high hematocrit (> 40%) with high recovery (up to 95%). Additionally, the washed RBCs post-cryopreserved are proved to maintain their morphology, mechanics, and functional properties. This may provide a nontoxic, high-efficiency, and glycerol-free approach for RBC cryopreservation, along with potential clinical transfusion benefits. Highlights: 1 We developed a novel method for high-efficiency, nontoxic, glycerol-free, scalable cryopreservation of human red blood cells with a high hematocrit (> 40%). 2 This method offered the potential for ultrafast and convenient applications by eliminating the need for permeable cryoprotectants, simplifying the washing steps, and reducing the washing time. 3 This method achieved a high RBC recovery of up to 95%, and the RBCs post-cryopreserved maintained their morphology, mechanics, and functional properties.